2019
DOI: 10.4251/wjgo.v11.i12.1141
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression trends of DNMT1 in gastrointestinal diseases: From benign to precancerous lesions to cancer

Abstract: BACKGROUNDIn recent years, the incidence of gastrointestinal (GI) cancer in China has increased annually. Early detection and appropriate therapy are considered to be the key to treat GI cancer. DNMT1 takes an active part in the advancement of GI cancer, which will change as the disease progresses. But its expression characteristics in the dynamic variations of GI carcinogenesis are still unclear.AIMTo investigate the expression characteristics of DNMT1 in different GI diseases.METHODSWe detected the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Then, both immunohistochemistry and bioinformatics analysis showed that DNMT1 expression is increased in GC tumour tissues compared with adjacent normal tissues, which is consistent with previous findings that DNMT1 is expressed at higher levels in early gastric cancer or high-grade intraepithelial neoplasia tissues compared to that in non-cancer mucosa or low-grade intraepithelial neoplasia tissues [ 37 ]. Mechanistically, H. pylori-induced chronic inflammation, but not H. Pylori itself, played a direct role in the induction of DNMT1 expression and aberrant DNA methylation in GC [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…Then, both immunohistochemistry and bioinformatics analysis showed that DNMT1 expression is increased in GC tumour tissues compared with adjacent normal tissues, which is consistent with previous findings that DNMT1 is expressed at higher levels in early gastric cancer or high-grade intraepithelial neoplasia tissues compared to that in non-cancer mucosa or low-grade intraepithelial neoplasia tissues [ 37 ]. Mechanistically, H. pylori-induced chronic inflammation, but not H. Pylori itself, played a direct role in the induction of DNMT1 expression and aberrant DNA methylation in GC [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…[10][11][12][13] Epidemiological data suggest that diabetes increases the relative risk of digestive cancers more than twofold, 1 and type 2 diabetes mellitus is associated with more aggressive digestive tract cancers. 14 Universal screening using potential biomarkers such as cancer antigen 19-9, carcinoembryonic antigens, or clinical tests (eg, computed tomography, endoscopic ultrasound, or magnetic resonance imaging) is not feasible, [15][16][17] as the existing biomarkers have limited diagnostic accuracy. Therefore, there is an urgent clinical need for novel prediction models and screening methods that are both efficient and cost-effective for the detection of asymptomatic cases.…”
Section: Introductionmentioning
confidence: 99%